An overview of the African genera of Prodidominae spiders: descriptions and remarks (Araneae: Gnaphosidae) - Rodrigues, Bruno V. B.; Rheims, Cristina A. (Zootaxa, 2020)
A taxonomic revision of exclusively African genera of Prodidominae (Gnaphosidae), with the exception of Theuma, is provided. Austrodomus Lawrence, 1947 is revised. The type species A. zuluensis Lawrence, 1947 is redescribed, the male of A. scaber (Purcell, 1904) is described for the first time, and one new species, A. gamsberg sp. nov. (♂), is described from Namibia. Katumbea Cooke, 1964 is considered a junior synonym of Austrodomus and A. oxoniensis (Cooke, 1964) comb. nov. from Tanzania is redescribed. Eleleis Simon, 1893 is revised. The type species, E. crinita Simon, 1893, is redescribed and eight new species are described: E. limpopo sp. nov. (♂♀) from South Africa and Zambia, E. okavango sp. nov. (♂♀) from Botswana and Namibia, E. etosha sp. nov. (♂♀), E. himba sp. nov. (♂) and E. luderitz sp. nov. (♀) from Namibia, E. leleupi sp. nov. (♂) and E. haddadi sp. nov. (♀) from South Africa, and E. solitaria sp. nov. (♀) from Cape Verde. Purcelliana Cooke, 1964 is revised. The type species, P. problematica Cooke, 1964, is redescribed and three new species are described: P. kamaseb sp. nov. (♂♀) and P. khabus sp. nov. (♂♀) from Namibia, and P. cederbergensis sp. nov. (♂) from South Africa. Plutonodomus Cooke, 1964 is redescribed based solely on the type species, P. kungwensis Cooke, 1964. In addition, three new genera are described: Kikongo gen. nov., to include K. ruwenzori sp. nov. (♂♀) and K. buta sp. nov. (♂♀) from the Democratic Republic of the Congo (D.R. Congo), and K. rutshuru sp. nov. (♂♀) from D.R. Congo and Kenya; Kituba gen. nov., to include K. mayombensis sp. nov. (♂♀) and K. langalanga sp. nov. (♀) from D.R. Congo; and Yoruba gen. nov., to include Y. ibadanus sp. nov. (♂♀) from Nigeria and Y. toubensis sp. nov. (♂♀) from Ivory Coast. Distribution maps are provided for the species discussed in this study and an identification key is provided for all twelve genera of Prodidominae recorded in Africa.